(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jHdZ QVGg hjeJQi GdeRjO efg hjSJhLH Hg CeG HYO , aEf Gddg bOQ GdCTjGA HbOQJg hOHQgG HMceJg s
(3BNQgG (B:s
(3hBNQgG eHJhQ , hGdehLhO efg ai HGH GdJaYjd bhdg (B: (3hjYRH ReGfkG Ci CbGe Ydi GdYRhHI s
(3cJHJ GdYfGhjf HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs